The health and development of children born to older mothers in the United Kingdom: observational study using longitudinal cohort data. - Sutcliffe, A; Barnes, J; Belsky, J; Gardiner, J; Melhuish, E (2012)
OBJECTIVE: To assess relations between children's health and development and maternal age. DESIGN: Observational study of longitudinal cohorts. SETTING: Millennium Cohort Study (a random sample of UK children) and the National Evaluation of Sure Start study (a random sample of children in deprived areas in England), 2001 to 2007. PARTICIPANTS: 31,257 children at age 9 months, 24,781 children at age 3 years, and 22,504 at age 5 years. MAIN OUTCOME MEASURES: Childhood unintentional injuries and hospital admissions (aged 9 months, 3 years, and 5 years), immunisations (aged 9 months and 3 years), body mass index, language development, and difficulties with social development (aged 3 and 5 years). RESULTS: Associations were independent of personal and family characteristics and parity. The risk of children having unintentional injuries requiring medical attention or being admitted to hospital both declined with increasing maternal age. For example, at three years the risk of unintentional injuries declined from 36.6% for mothers aged 20 to 28.6% for mothers aged 40 and hospital admissions declined, respectively, from 27.1% to 21.6%. Immunisation rates at nine months increased with maternal age from 94.6% for mothers aged 20 to 98.1% for mothers aged 40. At three years, immunisation rates reached a maximum, at 81.3% for mothers aged 27, being lower for younger and older mothers. This was linked to rates for the combined measles, mumps, and rubella immunisation because excluding these resulted in no significant relation with maternal age. An increase in overweight children at ages 3 and 5 years associated with increasing maternal age was eliminated once maternal body mass index was included as a covariate. Language development was associated with improvements with increasing maternal age, with scores for children of mothers aged 20 being lower than those of children of mothers aged 40 by 0.21 to 0.22 standard deviations at ages 3 and 4 years. There were fewer social and emotional difficulties associated with increasing maternal age. Children of teenage mothers had more difficulties than children of mothers aged 40 (difference 0.28 SD at age 3 and 0.16 SD at age 5). CONCLUSION: Increasing maternal age was associated with improved health and development for children up to 5 years of age.